Investigation on quality of hydroxyapatite adhesion on investment casting mould - Lotfabadi, Amir Fereidouni (2008)
Quality of Hydroxyapatite adhesion on investment casting mould was investigated in this project. Investment casting is a new method for HAp coating onto the metals. First stage of applying this method is making appropriate investment casting mould. Appropriate investment casting mould should have specific properties such as: sufficient strength, proper shape for obtaining sound casting, and the must important one, enough amount of HAp should adhered onto the inner layer of investment casting mould to defuse into the metal during casting for desirable coating. For this purpose appropriate methods used to stick sufficient amount of Hydroxyapatite onto inner layer of ceramic investment casting mould to prepare it for metal coating by casting. therefore 3 different HAp-water mixture viscosities: 5, 7.5 and 10 seconds, were applied to find out which of them was support enough amount of Hydroxyapatite after dewaxing and firing. Dewaxing in three different temperatures 100°, 200° and 300° C applied as well to investigate the effect of the dewaxing temperature on the quality of HAp adhesion on to the moulds. Finally after gathering the results of dewaxing; moulds that have the desirable properties were fired at 600° C to study the effect of firing process on the quality of hydroxyapatite adhesion on moulds. After all XRD, EDAX tests and 3D microscope supervision were done to find out the results. By considering these tests 5 seconds viscosity of HAp-water mixture and 300°C dewaxing temperature had the desirable properties for making sufficient investment casting moulds for metal coating.